Application of solar photocatalysis in the treatment of water for human consumption and wastewater - Gosgot Angeles, Wildor (2023)
The efficiency of disinfection of well water and degradation of organic matter of residual water of treatments by solar disinfection (SODIS-CPC) and photocatalysis (TiO2 in suspension [TiO2susp. - CPC], concrete catalyst mixed with TiO2 [CI- CPC] and concrete catalyst impregnated with TiO2 [CII-CPC]) coupled to a 1.15X compound parabolic collector (CPC 1.15X) and a 1.5 L PET bottle photoreactor. The evaluations were carried out in September and October. between 8:00 a.m. and 4:00 p.m., with solar radiation of less than 1000 W/m2. The results showed that the CII-CPC achieved a maximum efficiency of 99.99% of inactivation of total, fecal coliforms and E. coli in the well water. The SODIS-CPC had a maximum BOD and COD removal efficiency of 93.08 and 94.94 %, respectively. The disinfection and degradation efficiency depends on the intensity of the incident radiation, the exposure time, TiO2 concentration and the geometry of the reactor.